Depression and suicide in chronic medical illness: train the nurses for a mental health preparedness - Thomas, Tengsy; Atallah, Mohammed; Joseph, Manu K. (International Journal Of Community Medicine And Public Health, 2025)
Background: Depression and suicide occur as a comorbidity in chronic medical illness. The poor knowledge and attitude of staff nurses in general practice greatly impacts the identification and treatment of these patients. Training nurses on this will reduce the mortality related to this. The current study identified the effectiveness of a structured educational program in improving the knowledge and attitude of nursing personnel. Method: A true experimental study was performed on 120 staff nurses working in different medical units of a hospital in Saudi Arabia. The samples were randomly selected and allotted 60 in experimental and 60 in control group by randomization. Pretest posttest control group design was adopted, and a video assisted structured planned training program was provided for the interventional group and the mean difference was compared. Results: The knowledge of nurses on caring for patients with depression increased from preprogram to post program. (M =3.90 to 5.17 (t= 6.469, p<.001 and for suicide, from (M =2.13 to 2.53. The attitude towards depression increased from 24.60 to 27.03 and for suicide from (M =20.83, SD = 3.75) to (M =23.37, SD = 3.85); t =5.443, p <0.001. The mean post-test knowledge was higher in experimental group for all measures except for attitude on depression with a slight increase in control group. Conclusion: Our findings suggest PTP was effective in developing knowledge and attitude for nurses on managing depression and suicide in chronic medical areas.